2014
DOI: 10.1186/1756-0500-7-24
|View full text |Cite
|
Sign up to set email alerts
|

Re-organisation of oesophago-gastric cancer services in England and Wales: a follow-up assessment of progress and remaining challenges

Abstract: BackgroundThis study is an update on an earlier article in 2007 to assess the implementation of the Cancer Plan reform strategy in England and Wales.FindingsA national online survey to upper gastro-intestinal leads at network and trust level. The questionnaire was designed based on existing clinical practice guidelines and addressed governing principles and operational procedures related to the delivery of cancer care. It was sent in January 2012 to upper gastro-intestinal network and trusts leads at all cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…For example, 30-day mortality following gastrectomy was 4.5% in 2007–2009 in England ( Cromwell et al , 2010 ), compared with 12.0% in 24 hospitals in England and Wales in 1999–2002 ( McCulloch et al , 2003 ). It is likely this is partly due to the increase in the percentage of specialist centres that have three or more specialist surgeons (as per the guidelines) from 53% in 2007 to 95% in 2012, and partly because by 2012 nearly all stomach cancer patients eligible for curative treatment were seen by a specialist MDT ( Groene et al , 2014 ). Thirty-day postoperative mortality from colorectal cancer also declined from 6.8% in 1998 to 5.8% in 2006, with the biggest decline occurring in 2005–2006 ( Morris et al , 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, 30-day mortality following gastrectomy was 4.5% in 2007–2009 in England ( Cromwell et al , 2010 ), compared with 12.0% in 24 hospitals in England and Wales in 1999–2002 ( McCulloch et al , 2003 ). It is likely this is partly due to the increase in the percentage of specialist centres that have three or more specialist surgeons (as per the guidelines) from 53% in 2007 to 95% in 2012, and partly because by 2012 nearly all stomach cancer patients eligible for curative treatment were seen by a specialist MDT ( Groene et al , 2014 ). Thirty-day postoperative mortality from colorectal cancer also declined from 6.8% in 1998 to 5.8% in 2006, with the biggest decline occurring in 2005–2006 ( Morris et al , 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are still some examples of gastrectomy being under taken in low volume units reflecting inclusion within general surgery services. Nevertheless, the evidence of improved outcomes following centralization of services described in different studies has occurred [13][14][15]. The preoperative assessment of patients is similar with dedicated cardiopulmonary review.…”
Section: Discussionmentioning
confidence: 99%
“…The delay between onset of symptoms and diagnostic endoscopy has been highlighted in the UK. Strategies to minimise this delay including specification of local diagnostic units and specialist treatment centres for oesophageal and gastric cancer has resulted in an increase in access to curative treatment as well as a decrease in operative mortality [15,19]. In Denmark centralization of gastric cancer surgery has resulted in improvements in the quality of care and a reduction in 30-day postoperative mortality [18].…”
Section: Discussionmentioning
confidence: 99%
“…Another study from Wales showed that oesophageal cancer patients treated by multi-disciplinary teams experienced a lower postoperative mortality than control patients, and were more likely to survive 5 years (p<0.001) [17]. An organisational survey on the progress due to centralisation has shown that targets of minimum staffing levels have been achieved and the use of formal assessment of nutritional needs has improved [18]. In relation to the outcomes of surgery, a study examining the effect centralisation on O-G cancer services in Gloucester reported improvement in the median survival time and substantial reductions in 30 day post-operative mortality from 10.3% precentralisation to 3.6% post-centralisation (p = 0.006) [19].…”
Section: Previous Work and What Our Study Addsmentioning
confidence: 99%